Developing Windows 8 Metro apps with XAML and C♯ - Whittaker, Derik (LiveLessons (Indianapolis, Ind.), 2012)
"Windows 8/Metro is a whole new ecosystem for developers and a new ecosystem means new opportunities. Windows 7 is reported to be installed on over 450 million computers around the world and that number is only going to continue to grow. With Windows 8 Microsoft has re-imagined how the user experience should be for both tablet and desktop computers. With this they have also rebuilt their development platform and ecosystem. They have taken the current tablet User Experience conventions and taken to the next level, this next level is Metro. In the Metro UI users will experience a whole new way to use applications. These applications will be multi-touch enabled and very engaging. The approach for this video training is to create a series of standalone lessons which will walk the user through the various topics. These lessons will be very heavily focused on writing code and generating small workable applications. At the end of every lesson there will be a sample application produced which can be used as a point of reference for the viewers to better understand the concepts."--Resource description page (viewed 22 June 2012).